Connection between the capture of virtual space and personal self-realization of youth - Golovanova, Tetiana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The relevance of studying the process of personal self-realization under the conditions of the modern transformed society is stipulated both by the need for effective adaptation to changes in the social environment, and by the need of the society for the fullest possible actualization and unlocking creative potential of citizens. Due to the process of individual self-realization a single person gets involved into public relations. Therefore, the problem of personal self-realization belongs to basic problems of human existence. In this article self-realization in virtual space will be considered as exemplified in adolescence.Adolescent psychology is one of the most complex and least elaborated sections of developmental psychology.Studying the impacts of the virtual environment on personal self-realization is relevant in the modern world due to the fact that this environment becomes quite significant, and sometimes dominant, in the realities of the information society. The group under investigation in this research: Internet users aged 16 to 25. The research was conducted involving 223 subjects under investigation.The research program was as follows: I. Preparatory stage. Research planning. The group under investigation in this research: Internet users aged 16 to 25. The research was con- ducted involving 223 subjects under investigation.II. Main stage. The research process: The Internet Addiction Test according to Kimberly Young' procedure will be offered for completion by the adolescents. 100 people with the score of more than 49 points will be selected based on the results of this test. The Self-Actualization Test (SAT), the situational self-actualization diagnostic technique and the questionnaire will be offered for completion by the persons who were selected during the background research. 100 of the respondents with less than 49 points according to Kimberly Young's procedure will be selected to pass the Self-Actualization Test (SAT) as a control group.II. Main stage. Data collection. The process of direct investigation involves the researcher's contact with the research subject, which results in obtaining a set of characteristics of that subject. The characteristics obtained are the main material to test the working hypothesis and solve the problem. The respondents were sent all necessary instructions via the Internet. The completed questionnaire data was received in the same way.After conducting a background research, a sample of 100 respondents with the Internet addiction score higher than 49 was formed. In addition, a control group of 100 respondents with the Internet addiction score lower than 49 was formed.III. Final stage. Data processing. Having collected the set of data, the researcher starts processing them obtaining higher level information which is subject to further interpretation. The following statistical data processing methods were used in the research: the Student's t-test, Pearson's correlation coefficient.The following dependences were discovered as a result of the analysis and calculation of the statistical dependences:• The connection between preoccupation with virtual space and self-realization of an active Internet adolescent user was established at the 99.9% level of significance.• With the increase in time that a person spends in virtual space, his/her self-realization level reduces with the 95% significance level for Inter- net-addicted individuals who mainly use virtual space for online games. For people who use virtual space for another purpose, the increase in time has no direct impact on self-realization.
Keywords: self-realisation; actualization; virtual space; youth age; Internet addiction; personality